Metabolic Profiling and Integration of Metabolomic and Transcriptomic Data From Pectoralis Muscle Reveal Winter-Adaptive Metabolic Responses of Black-Capped Chickadee and American Goldfinch - Wone, Bernard W. M.; Swanson, David L. (Frontiers in Ecology and Evolution, 2022)
Seasonal changes, such as alterations in food availability or type and cold conditions, present challenges to free-living birds living in highly seasonal climates. Small birds respond to such challenges through seasonal metabolic flexibility, which better matches seasonal metabolic phenotypes to environmental conditions and can improve fitness. To better understand the mechanistic basis of this metabolic flexibility, we conducted a large-scale metabolic profiling of pectoralis muscle in black-capped chickadees (Poecile atricapillus) and American goldfinches (Spinus tristis), which are small, year-round bird species of temperate-zones. We analyzed muscle samples using non-biased, global metabolomics profiling technology based on UHLC/MS/MS2 and GC/MS platforms. A total of 582 metabolites was characterized for summer and winter season samples. Chickadees showed greater seasonal separation of global metabolite profiles than goldfinches, which is consistent with previous transcriptomic studies of pectoralis muscle in these two species. Reduced levels of amino acids during winter occurred in both species and might reflect decreasing dietary protein intake, amino acid shuttling to other pathways for thermogenesis and/or elevated rates of protein turnover in the pectoralis muscle. Concomitant decreased abundances in TCA cycle metabolites suggest faster cycling of the oxidative phosphorylation pathway in winter to meet the metabolic demands of thermogenesis. Accordingly, chickadees displayed shifts toward lipid oxidation in winter, whereas goldfinches showed winter declines in ketone bodies, which suggests increased energy demand or subtle changes in substrate availability. Beyond the winter-specific changes in metabolite abundances, integration of the metabolomic and the transcriptomic data revealed a landscape of gene–metabolite associations related to the winter-adaptive metabolic response. This landscape of gene–metabolite pairs was overrepresented by pathways associated with transport of small molecules, metabolism of amino acids and derivatives, activation and biosynthesis of fatty acid derivatives, and biosynthesis and metabolism of nicotinate and nicotinamide derivatives. Collectively, our results suggest that increased levels of NADH and its derivatives in the pectoralis muscle are a potential novel mechanism for increasing winter metabolic output, fueled by lipids, for thermogenesis during winter.